Coagulopathy biomarkers in mild to moderate CoVID-19 patients admitted in a tertiary care public hospital in eastern India - Santasmita Pal; Subhayan Lahiri; Kuntal Bhattacharyya; Amrita Ghosh; Tapan Mukhopadhyay (Al Ameen Medical College, 2021)
Background: The present study was undertaken to identify various prognostic biomarkers related to coagulation that may predict the outcome of mild to moderate CoVID-19 patients. Objectives: The biomarkers aPTT, PT, INR, D-Dimer, Procalcitonin, Ferritin were studied with their interdependence on each other and with their severity in the CoVID-19 patients. Methods: An analytical cross-sectional study was conducted at the department of Biochemistry, and Indoor medical wards of Medical College & Hospital, Kolkata from June 2020 to December 2020 among 120 adult consecutive consenting mild to moderate patients with documented history and diagnosis of CoVID-19. Statistical analysis was done to find association of these coagulation parameters and their significant correlation to prognosticate severity of CoVID-19. Results: Highest numbers of cases were from 51-60 years age group, followed by 21-30 and 31-40 years with almost equal gender distribution; unfavourable findings were more in males in all age groups except 31-40 years, not statistically significant. Activated partial thromboplastin time (aPTT), Prothrombin time (PT), Procalcitonin (PCT), D-dimer levels were significantly higher in mild and moderate CoVID-19 cases; gender-wise difference was significant only in PCT and D-dimer levels. Ferritin levels were higher, with no significant differences in age and gender. Conclusions: Procalcitonin and D-dimer were superior biomarkers to predict severity in COVID-19 patients. These observations need further evaluation with systems approach.